A strategic approach to the synthesis of ferrocene appended chalcone linked triazole allied organosilatranes: Antibacterial, antifungal, antiparasitic and antioxidant studies. Issue 1 (1st January 2019) - Singh, Gurjaspreet; Arora, Aanchal; Kalra, Pooja; Maurya, Indresh Kumar; Ruizc, Cristobal Espinosa; Estebanc, M. Angeles; Sinha, Shweta; Goyal, Kapil; Sehgal, Rakesh
Graphical abstract: Abstract: A series of ferrocene appended chalcone allied triazole coupled organosilatranes (FCTSa7 –FCTSa12 ) were synthesised with the aim of amalgamating the pharmacological action of the constituting moieties into a single molecular scaffold. All the synthesised silatranes were well characterized by various spectroscopic techniques like IR, 1 H NMR, 13 C NMR and elemental analysis. Organosilatranes were then evaluated for their biological alacrity against bacterial and fungal strains compared with the standard drugs Rifampicin and Amphotericin B respectively. The ferrocene conjugates were found to be only moderately effective against the tested microbes. However, the organosilatranes conceded excellent efficacy against parasite G. lamblia with FCTSa11 arraying the leading results. On the other hand against another parasite T. vaginalis, FCTSa8 has emerged as an outstanding composite. Further, Total Antioxidant Assay (TAA) with 2, 2′-azino-bis-3-(ethylbenzothiazoline-6-sulphonic acid) revealed FCTSa10 to be the best claimant for radical scavenging activity. Along these lines, introducing some different substituents in the synthesised hybrids may act as a useful strategy for increasing the biological profile of the drugs.